An Application of Web-Based E-Learning in Online Learning for Students at Future High School Libya - Ali, Ahmad (Bulletin of Science Education, 2022)
In 2020 School at Libya implemented online learning from home due to the Covid-19 pandemic, but teachers and students continue to carry out online-based learning through applications, for instance web-based e-learning. The article aimed to analyze an application web-based e learning on the students’ Future High School Libya. The method used qualitative, by using questionnaire via Google Form as collecting the data to students at future high school libya. The data obtained were analyzed and calculated on the average using a Likert scale and modified to represent the criteria for assessment and the final results were described. The result showed that learning using eeb-based e-learning in online learning in all subjects has been effective and can be used as a learning application during the Covid-19 pandemic with percentage 75%. This of course could not be separated from the roles of teachers in the learning implementation process. In this learning systematics the teacher not only provides teaching materials, but also adds learning media that interesting enough. Keywords: Online Learning, Web-Based Learning, Application E-Learning